Neurosteroid Influences on Sensitivity to Ethanol - Helms, Christa M.; Rossi, David; Grant, Kathleen A. (Frontiers in Endocrinology, 2012)
This review will highlight a variety of mechanisms by which neurosteroids affect sensitivity to ethanol, including physiological states associated with activity of the hypothalamic–pituitary–adrenal (HPA) and hypothalamic–pituitary–gonadal (HPG) axes, and the effects of chronic exposure to ethanol, in addition to behavioral implications. To date, γ-aminobutyric acid (GABAA) receptor mechanisms are a major focus of the modulation of ethanol effects by neuroactive steroids. While NMDA receptor mechanisms are gaining prominence in the literature, these complex data would be best discussed separately. Accordingly, GABAA receptor mechanisms are emphasized in this review with brief mention of some NMDA receptor mechanisms to point out contrasting neuroactive steroid pharmacology. Overall, the data suggest that neurosteroids are virtually ubiquitous modulators of inhibitory neurotransmission. Neurosteroids appear to affect sensitivity to ethanol in specific brain regions and, consequently, specific behavioral tests, possibly related to the efficacy and potency of ethanol to potentiate the release of GABA and increase neurosteroid concentrations. Although direct interaction of ethanol and neuroactive steroids at common receptor binding sites has been suggested in some studies, this proposition is still controversial. It is currently difficult to assign a specific mechanism by which neuroactive steroids could modulate the effects of ethanol in particular behavioral tasks.